Reptiles of the Unión river basin, Valle de El General, Costa Rica (UNED Research Journal, 2016)
Reptiles are unappreciated, mainly for their appearance, yet they have important functions in ecosystems, such as population control and as food for other species. I made monthly surveys (June 2014 to June 2015) in 20 sectors (15X200 m each) on both sides of Unión river in southern Costa Rica, along 12 km transects. I found 24 species of reptiles; one introduced, one endemic and three that range between Nicaragua and Panama; by group: nine snakes, one turtle, and 12 lizard iguana. Some, especially snakes, are killed by the settlers, even though most are not poisonous. This knowledge will be important in the management and conservation of watersheds in southern Costa Rica.
Keywords: snake; turtle; iguana; lizard; watershed; conservation